Kehidupan Harun a.s. dan Dakwahnya - Muhammad, Muhammad Thaib (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2021)
Allah SWT has informed through the Qur'an many stories of the previous people, whether it is the story of the people who are obedient to Allah SWT or the story of the people who do not obey. For every Ummah, Allah SWT has sent prophets and apostles to preach so that they always obey Allah SWT. Likewise, Allah SWT has sent Musa a.s and Harun a.s to the Israel generation and the Qibthi who inhabited Egypt. In carrying out his da'wah, Moses or Musa a.s had prayed for Allah SWT to make Harun a.s. be appointed as a prophet and then Allah SWT granted. So Allah SWT gave him the advantage of eloquence in speech and brilliance in thinking so that he could help Musa a.s. in his da'wah. This short article will specifically discuss the story of the Prophet Harun a.s as narrated in the Qur'an.Â ABSTRAKAllah SWT telah menginformasikan melalui Al-Qur'an banyak kisah orang-orang terdahulu, baik itu kisah orang-orang yang taat kepada Allah SWT maupun kisah orang-orang yang tidak taat. Bagi setiap umat, Allah SWT telah mengutus para nabi dan rasul untuk berdakwah agar selalu taat kepada Allah SWT. Demikian juga Allah SWT telah mengutus Musa a.s dan Harun a.s kepada generasi Israel dan Qibthi yang mendiami Mesir. Dalam menjalankan dakwahnya, Musa atau Musa a.s telah berdoa kepada Allah SWT agar Harun a.s. diangkat menjadi nabi dan kemudian dikabulkan Allah SWT. Maka Allah SWT memberinya kelebihan kefasihan dalam berbicara dan kecemerlangan dalam berpikir sehingga ia dapat membantu Musa a.s. dalam dakwahnya. Artikel singkat ini secara khusus akan membahas kisah Nabi Harun a.s sebagaimana diriwayatkan dalam Al-Qur'an.